Multi-scale damage analysis and fatigue behavior of PLA manufactured by fused deposition modeling (FDM). Issue 2 (11th January 2021) - Vanaei, Hamid Reza; Shirinbayan, Mohammadali; Vanaei, Saeedeh; Fitoussi, Joseph; Khelladi, Sofiane; Tcharkhtchi, Abbas
Abstract : Purpose: Fused deposition modeling (FDM) draws particular attention due to its ability to fabricate components directly from a CAD data; however, the mechanical properties of the produced pieces are limited. This paper aims to present the experimental aspect of multi-scale damage analysis and fatigue behavior of polylactic acid (PLA) manufactured by FDM. The main purpose of this paper is to analyze the effect of extruder temperature during the process, loading amplitude, and frequency on fatigue behavior. Design/methodology/approach: Three specific case studies were analyzed and compared with spool material for understanding the effect of bonding formation: single printed filament, two printed filaments and three printed filaments. Specific experiments of quasi-static tensile tests coupled with microstructure observations are performed to multi-scale damage analysis. A strong variation of fatigue strength as a function of the loading amplitude, frequency and extruder temperature is also presented. Findings: The obtained experimental results show the first observed damage phenomenon corresponds to the inter-layer bonding of the filament interface at the stress value of 40 MPa. For instance, fatigue lifetime clearly depends on the extruder temperature and the loading frequency. Moreover, when the frequency is 80 Hz, the coupling effect of thermal and mechanical fatigue causes self-heating which decreases the fatigue lifetime. Originality/value: This paper comprises useful data regarding the mechanical behavior and fatigue lifetime of FDM made PLA specimens. In fact, it evaluates the effect of process parameters (extruder temperature) based on the nature of FDM that is classified as a thermally-driven process.